The Red Pony Movie Still - Chas. K. Feldman Group Productions, Incorporated; Republic Pictures; Viacom/Paramount Pictures:::Creator::::::::::::
Tom, aka Jody Tiflin (Peter Miles) in muddy corral facing a girl and her friends on a horse. RESTRICTED USE